Use of Big Data and Business Intelligence Platforms to Boost the Tourism and Travel Sector in the Province of Fianarantsoa, Madagascar - Razafindrazanakolona A.D.; Raharijaona A.; Rakotonirina M. D. L.; Ramanampisoa V.E.; Rabesiaka R.; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B.; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2023)
The dynamization of Tourism in the Haute Matsiatra Region (Isalo, Andringitra, Ranomafana) is considered favorable to the promotion of Tourism and important for the sustainable development of the rural areas concerned. They are exploited by local visitors. However, currently, there is an inspiration for new openings and new and more original horizons throughout Madagascar. The idea of launching the